An Empirical Examination of the Structural Stability of Disaggregated U.S. Import Demand - Deyak, Timothy A.; Sawyer, W. Charles; Sprinkle, Richard L. (The Review of Economics and Statistics, 1989)
Timothy A. Deyak, W. Charles Sawyer, Richard L. Sprinkle, An Empirical Examination of the Structural Stability of Disaggregated U.S. Import Demand, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 337-341